2022
DOI: 10.33448/rsd-v11i12.33870
|View full text |Cite
|
Sign up to set email alerts
|

Respuesta del cultivo del tomate (Solanum lycopersicum L.) a la aplicación de QuitoMax® en condiciones de salinidad

Abstract: Se estudió el efecto del QuitoMax® en el comportamiento de plantas de tomate de las variedades Claudia y Amalia en condiciones estrés salino. El experimento se desarrolló en el municipio Cauto Cristo provincia de Granma en el período de octubre de 2017 a marzo de 2018, en un suelo clasificado como salino sódico (CE 4 dS m-1).  El diseño experimental utilizado fue de bloques al azar, con arreglo factorial, replicando cuatro veces cada variante. Se aplicó el bioestimulante a los 12 días después del trasplante (D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Its use stimulates initial seed germination, flowering and fruit filling (Reyes-Pérez et al, 2020). QuitoMax ® has also been used in tomato and has caused an acceleration of plant metabolism and an increase of 15% in yield under saline soil (Avila-Amador et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its use stimulates initial seed germination, flowering and fruit filling (Reyes-Pérez et al, 2020). QuitoMax ® has also been used in tomato and has caused an acceleration of plant metabolism and an increase of 15% in yield under saline soil (Avila-Amador et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…For example, in beans (Phaseolus vulgaris), corn (Zea mays), potato (Solanum tuberosum), tobacco (Nicotiana tabacum) and tomato, González et al (2021) reported an increase in biomass and yield of approximately 17% under field conditions but not under salinity. Some of the most recent reports of its use for saline stress mitigation were developed by Avila-Amador et al (2022) but were based on morphological and agronomical indicators. In this sense, our hypothesis is that QuitoMax ® minimizes the effects of soil salinity and promotes biochemical activity in tomato plants.…”
Section: Introductionmentioning
confidence: 99%